PENGARUH PEMBERIAN BUBUK DAUN KEMANGI DAN SUKU TERHADAP POPULASI Sitophilus zeamais DAN KUALITAS BENIH JAGUNG YANG DISIMPAN - Rahmawati, Fauziah; Solichah, Chimayatus (Jurnal Agrivet, 2025)
Damage to stored corn seeds due to the pest Sitophilus zeamais can be suppressed by control. One of alternative to pest control is using botanical pesticides with basil and breadfruit leaf powder. This study aims to determine the effect composition and type of leaf powder in suppressing of Sitophilus zeamais. The research was conducted in February to April 2024 at Plant Protection Laboratory, UPN "Veteran" Yogyakarta. The research method used a Complete Random Design with 6 treatments and 4 repetitions. There are 6 treatments of the composition basil and breadfruit leaf powder namely control; 1:0; 0:1; 1:1; 2:1; and 1:2. The analysis used ANOVA, followed by the DMRT at 5%, and continued with the Orthogonal Contrast test at 5%.The data from study showed that the composition of basil and breadfruit leaf powder was suppressing S. zeamais and maintaining the quality of seeds in storage by increasing mortality, number of living imago of S. zeamais, and efficacy. The most effective leaf powder and composition in suppressing S. zeamais is the composition of basil and breadfruit leaf powder 1:1 which can increase the mortality of S. zeamais by up to 100% after application. There were differences in mortality, number of living imago of S. zeamais, and efficacy of the control treatment.